Systematic Literature review: Approach, Challenges an Further of Continous Improvement in private sector - Indrijawati, Aini; Mediaty, Mediaty; Assaggaf, Aswar Anas; Hastuti, Hastuti; Rosali, Suryarahma; Sriwahyuni, Sriwahyuni (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This research aims to analyse the approaches, challenges, and prospects of implementing Continuous Improvement (CI) in the private sector through the Systematic Literature Review (SLR) method. By collecting and evaluating 42 relevant articles, the study found that CI approaches involve methods such as Lean Manufacturing, Six Sigma, Total Quality Management (TQM), and Kaizen. The main challenges identified include resistance to change, limited resources, and lack of top management support. The future outlook for CI is expected to focus more on the integration of advanced technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), and environmental sustainability. The results of this study provide an in-depth understanding of CI implementation in improving the efficiency and competitiveness of companies in the private sector.